2014
DOI: 10.1007/s12013-014-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Endothelin-Induced Myocardial Hypertrophy in Rats and the Mechanism Involved

Abstract: The aim of the study was to evaluate the clinical efficacy of hydrogen sulfide (H2S) treatment on the endothelin-induced cardiac hypertrophy. Sixty-four adult male rats, weighing from 180 to 200 g, were randomly divided into four groups: ten in normal group, ten in sham group, 44 in model group established by inducing the myocardial hypertrophy with endothelin. The myocardial hypertrophy model rats were randomly divided into two groups: 22 in the simple myocardial hypertrophy model group and 22 in the H2S trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, pharmacologic H 2 S therapy during heart failure serves to mitigate pathological left ventricular remodeling and reduce myocardial hypertrophy, oxidative stress, and apoptosis [ 49 ]. In an endothelin-induced cardiac hypertrophy rat model, Yang et al [ 57 ] found that H 2 S treatment could decrease left ventricular mass index, volume fraction of myocardial interstitial collagen, and myocardial collagen content and improve cardiac hypertrophy. In another hypertrophy model induced by abdominal aorta coarctation, Huang et al [ 58 ] revealed that exogenous administration of H 2 S significantly suppressed the development of cardiac hypertrophy and also greatly downregulated the Ang-II levels in cardiac tissue, suggesting that H 2 S plays a pivotal role in the development of pressure overload-induced cardiac hypertrophy.…”
Section: Role Of H 2 S In Heart Diseasesmentioning
confidence: 99%
“…In addition, pharmacologic H 2 S therapy during heart failure serves to mitigate pathological left ventricular remodeling and reduce myocardial hypertrophy, oxidative stress, and apoptosis [ 49 ]. In an endothelin-induced cardiac hypertrophy rat model, Yang et al [ 57 ] found that H 2 S treatment could decrease left ventricular mass index, volume fraction of myocardial interstitial collagen, and myocardial collagen content and improve cardiac hypertrophy. In another hypertrophy model induced by abdominal aorta coarctation, Huang et al [ 58 ] revealed that exogenous administration of H 2 S significantly suppressed the development of cardiac hypertrophy and also greatly downregulated the Ang-II levels in cardiac tissue, suggesting that H 2 S plays a pivotal role in the development of pressure overload-induced cardiac hypertrophy.…”
Section: Role Of H 2 S In Heart Diseasesmentioning
confidence: 99%
“…H 2 S attenuated phenylephrine‐induced cardiomyocyte hypertrophy via improved glucose metabolism or up‐regulation of mir‐133 (Liu et al , ; Liang et al , ). H 2 S also prevented endothelin‐ or smoking‐induced enhancement of left ventricular mass (Yang et al , ; Zhou et al , ). H 2 S attenuated myocardial hypertrophy induced by abdominal aortic constriction in rats, through connexin 43 up‐regulation (Huang et al , ).…”
Section: Introductionmentioning
confidence: 98%
“…Studies showed that H 2 S had a protective effect on myocardial injury in different diseases (Liu et al, 2014; Shen et al, 2015). H 2 S protected the myocardium and cardiac function by inhibiting inflammatory reaction and apoptosis, etc (Sodha et al, 2009; Su et al, 2009; Wei et al, 2010; Lu et al, 2013; Yang et al, 2014). Furthermore, our previous studies demonstrated that down-regulation of renal H 2 S/CBS pathway induced by high salt led to the development of hypertension, and H 2 S could improve aortic structural remodeling and reduce the high salt-induced renal injury in Dahl rats (Huang et al, 2015, 2016), suggesting that the effect of H 2 S on the function and structure of aorta and kidney participated in the protective regulation of H 2 S on the myocardial hypertrophy.…”
Section: Introductionmentioning
confidence: 99%